Interaction of hydrogen with au modified by Pd and Rh in view of electrochemical applications - Juarez, Maria Fernanda (2016)
Hydrogen interaction with bimetallic Au(Pd) and Au(Rh) systems are studied with the density functional theory (DFT)-based periodic approach. Several bimetallic configurations with varying concentrations of Pd and Rh atoms in the under layer of a gold surface(111) were considered. The reactivity of the doped Au(111) toward hydrogen adsorption and absorption was related to the property modifications induced by the presence of metal dopants. DFT-computed quantities, such as the energy stability, the inter-atomic and inter-slab binding energies between gold and dopants, and the charge density were used to infer the similarities and differences between both Pd and Rh dopants in these model alloys. The hydrogen penetration into the surface is favored in the bimetallic slab configurations. The underlayer dopants affect the reactivity of the surface gold toward hydrogen adsorption in the systems with a dopant underlayer, covered by absorbed hydrogen up to a monolayer. This indicates a possibility to tune the gold surface properties of bimetallic electrodes by modulating the degree of hydrogen coverage of the inner dopant layer(s)